Negotiating Islamic Business Ethics in TikTok Live Streaming: Evidence from Aglaonema Micro, Small, and Medium Enterprises - jati Imantoro; Kucoro Budi Riyanto; Andiana Rosid (Journal of Contemporary Applied Islamic Philanthropy, 2026)
Purpose: This study aims to analyze how Islamic business ethics negotiations occur in the practice of TikTok live streaming in MSMEs selling aglaonema, as well as how business actors balance ethical principles and the demands of digital platform performance. Previous studies on live streaming commerce have primarily focused on consumer behavior and marketing effectiveness, while limited attention has been given to how Islamic business ethics are negotiated by MSME actors in real-time digital interactions. Methodology: The research uses a qualitative approach with an interpretive paradigm and case study design. The research subjects consisted of six informants, namely five owners and one live streaming host, who were selected purposively. Data collection was carried out through in-depth interviews, live streaming observations, and documentation, then analyzed using thematic analysis techniques assisted by NVivo 12 Plus software. Findings: The results show that ethical negotiations occur dynamically in real-time interactions, influenced by sales pressure, platform algorithms, and audience responses. Business actors use various strategies such as persuasive communication, interaction adjustment, and product transparency to maintain ethical values such as honesty, trust, and responsibility. In addition, a balance between ethics and performivity is achieved through the integration of business practices that maintain moral principles while meeting the demands of the digital market. The conclusion of this study emphasizes that Islamic business ethics in live streaming commerce are adaptive and contextual, and can go hand in hand with digital marketing strategies without having to contradict each other.